The Effect of the Problem-Based Learning (PBL) Model on the Learning Outcomes of IPAS in Fifth Grade Students at SDN 20 Sintuk and SDN 15 Ampalu, North Pariaman District - Safitri, Ulandari; Isriani , Weni Putri (The Future of Education Journal, 2026)
Low learning outcomes in IPAS at the elementary school level remain a major problem, particularly due to the dominance of teacher-centered learning models that limit students’ active participation. This study aimed to examine the effect of the Problem Based Learning (PBL) model on IPAS learning outcomes of fifth-grade students at SDN 20 Sintuk and SDN 15 Ampalu, Pariaman Utara District. This research employed a quantitative approach using a pre-experimental method with a Static Group Comparison Design. The population consisted of all fifth-grade students from both schools, and the samples were selected using a saturated sampling technique. SDN 20 Sintuk was assigned as the experimental class taught using the Problem Based Learning model, while SDN 15 Ampalu served as the control class taught using conventional learning. Data were collected through IPAS learning outcome tests and analyzed using a t-test. The results showed that the average post-test score of the experimental class was 79, while the control class obtained an average score of 63. Hypothesis testing indicated that the calculated t-value (2.64) was greater than the t-table value (1.68) at a significance level of 0.05. These findings indicate that the Problem Based Learning model has a significant effect on improving IPAS learning outcomes of fifth-grade elementary school students. Keywords: Problem Based Learning; IPAS Learning Outcomes; Elementary School